2016
DOI: 10.1111/jav.00839
|View full text |Cite
|
Sign up to set email alerts
|

Female collared flycatchers choose neighbouring and older extra‐pair partners from the pool of males around their nests

Abstract: Extra‐pair copulation is common among passerine birds. Females might engage in this behavior to obtain direct or indirect benefits. They may choose extra‐pair males with larger ornaments, especially if they are costly to produce. Here we studied extra‐pair paternity in the collared flycatcher. Genetic analysis allowed us to identify the presence or absence of extra‐pair young in the focal nests, and to identify extra‐pair fathers. We also identified potential males available as extra‐pair sires around the nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Age is a key phenotypic trait that appears to underlie considerable individual variation in extra‐pair reproduction (Hamilton & Zuk, 1982; Hsu, Schroeder, Winney, Burke, & Nakagawa, 2015; Morton, Forman, & Braun, 1990; Westneat & Stewart, 2003). Numerous single‐species studies have shown a positive association between male age and within‐ or extra‐pair paternity success, or both (e.g., Edme, Munclinger, & Krist, 2016; Kempenaers, Verheyen, & Dhondi, 1997; Richardson & Burke, 1999; Westneat, 1990). Furthermore, meta‐analyses have shown that, across species, extra‐pair sires are often older than the males they cuckold (Ackay & Roughgarden, 2007; Hsu et al., 2015) and that EPP success is positively related to male age (Cleasby & Nakagawa, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Age is a key phenotypic trait that appears to underlie considerable individual variation in extra‐pair reproduction (Hamilton & Zuk, 1982; Hsu, Schroeder, Winney, Burke, & Nakagawa, 2015; Morton, Forman, & Braun, 1990; Westneat & Stewart, 2003). Numerous single‐species studies have shown a positive association between male age and within‐ or extra‐pair paternity success, or both (e.g., Edme, Munclinger, & Krist, 2016; Kempenaers, Verheyen, & Dhondi, 1997; Richardson & Burke, 1999; Westneat, 1990). Furthermore, meta‐analyses have shown that, across species, extra‐pair sires are often older than the males they cuckold (Ackay & Roughgarden, 2007; Hsu et al., 2015) and that EPP success is positively related to male age (Cleasby & Nakagawa, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are possible benefits that older males might provide to their mates (Brooks & Kemp, ; Edme, Munclinger, & Krist, ; Jones, Balmford, & Quinnell, ), males suffer from reduced reproductive success as they age in many species (Bonduriansky & Brassil, ; Ramasamy, Chiba, Butler, & Lamb, ; Schafer & Uhl, ; Sharma et al., ). There are various causes for the decline in reproductive output in males, for example, the accumulation of (often deleterious) mutations in a male's germ line during ageing (Pizzari, Dean, Pacey, Moore, & Bonsall, ) and resulting female choice acting against older males (Radwan, Michalczyk, & Prokop, ).…”
Section: Introductionmentioning
confidence: 99%
“…Females that are mated to high-quality social partners will likely need to travel farther away to find even better extra-pair males [31], and males surrounded by neighbors of lower quality can increase their opportunities to obtain extra-pair copulations [34]. Studies on extra-pair copulation have provided a great deal of evidence for female preference for high-quality males [55].…”
Section: Introductionmentioning
confidence: 99%
“…Males have developed pre- and post-copulatory strategies to decrease the risk of paternity loss in their own nests, such as mate guarding, frequent within-pair copulation, and direct physical punishment of the female [ 19 – 22 ]. The effectiveness of male paternity assurance strategies, however, can be affected by either individual female and male qualities, e.g., a male’s ability to guard and a female’s ability to evade her mate [ 1 , 23 25 ], or by the male’s costs of paternity assurance [ 26 28 ] and female experience [ 29 – 31 ]. Additionally, the effectiveness of male paternity assurance strategies can be precluded by ecological or social factors, such as intense nest site competition [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation